The use of micro-electro mechanical systems in vascular monitoring: implications for clinical use. (1st September 2016) - Pourriahi, Mahyar; Gurman, Pablo; Daich, Jonathan; Cynamon, Philip; Richler, Aaron; Elman, Noel; Rosen, Yitzhak
ABSTRACT: Introduction: BioMEMS relates to the implementation of Micro-Electro-Mechanical Systems (MEMS), in the biological and medical sphere. BioMEMS sensors are being utilized for many clinical applications, including a wireless urinary pressure system, right heart pressure sensor, and measurements on shearing force on the vascular system An important application of BioMEMS is on Heart failure (HF), a common disease, with a prevalence of 10% or more in persons 70 years of age or older, associated with high morbidity and mortality. HF affects over 5 million people and contributes to over 200, 000 deaths a year in the United States alone. Areas covered: The purpose of this paper is to provide a short overview on the successful implementation of BioMEMS sensors in heart failure and vascular medicine. Expert commentary: BioMEMS devices have overcome current limitations in pharmacotherapies for resistant hypertension by electrical modulation of the baroreceeptors. This represents a step towards the development of biomedical micro-devices for those conditions in which pharmacotherapies result poorly effective or elicit unacceptable toxicity.